Testing the hypothesis of a matter density discrepancy within Λ CDM model using multiple probes - Sakr, Ziad (Physical review, 2023)
We investigate whether the two cosmological discrepancies on the Hubble constant (H0) and the matter fluctuation parameter (σ8) are suggesting and compatible with the existence of an additional one on the present value of the matter density (ΩM). Knowing that the latter effects on observables is degenerate with those coming from H0 and σ8, we combined different probes in a way to break these degeneracies while adopting the agnostic approach of, either relaxing the calibration parameters in each probe in order to be set by the data, or by only including priors with the condition that they are obtained independently from the discrepant parameters. We also compiled and used a dataset from previous direct measurements of ΩM obtained in a model independent way using the Oort technique. We found when combining, as our baseline, galaxy cluster counts+cluster gas mass fraction probe+cosmic chronometers+direct ΩM+ priors from BBN and CMB, that both parameters, H0 and σ8, are consistent with those inferred from local probes, with σ8=0.745±0.05 while H0=73.8±3.01, and that for a value of ΩM=0.22±0.01 at more than 3σ from that usually determined by cosmic microwave background (CMB). We also found similar preferences when replacing cosmic chronometers (CC) by the supernovae (SN) data while allowing its calibration parameter to vary. However discrepancies appeared when we combined SN in addition to CC suggesting either inconsistencies between the SN sample and the other probes used or a serious challenge to our hypothesis. To further investigate the later, we performed some stress tests by adding constraints from baryonic acoustic oscillations and found that H0 reverts back to lower values at the expense however of a value of σ8 noncompatible with its local inferred ones, while only a prior on the matter density obtained from the CMB data keeps σ8 within the values usually obtained when adopting the calibration parameters of the low redshift growth of structures probes. We conclude from our adopted analysis that, either both tensions are compatible with the local inferred low values of matter density at odd with those obtained by CMB, reviving by then an overlooked discrepancy, or that further evidences are indicating that the Λ cold dark matter model is facing more difficulties to accommodate simultaneously all the current available observations.
Gesehen am 10.05.2024